Rheum turkestanicum rhizomes possess anti-hypertriglyceridemic, but not hypoglycemic or hepatoprotective effect in experimental diabetes - Mousa-; Ziba Rajaei; Esmaeil Khodaei; Maryam Malek; Habib Ghanbari (Mashhad University of Medical Sciences, 2017)
Objective: Rheum turkestanicum (R. turkestanicum) rhizomes have been used in Iranain traditional medicine as an anti-diabetic agent. The purpose of the present investigation was to evaluate the anti-diabetic and antioxidant activities of R. turkestanicum rhizome extract in streptozotocin-induced diabetic rats.Materials and Methods: Diabetes was induced by a single intraperitoneal injection of 55 mg/kg streptozotocin in male Wistar rats. Diabetic rats received the decoction extract of R. turkestanicum rhizomes at the doses of 200, 400 and 600 mg/kg daily by gavage for 3 weeks. Serum glucose and lipid levels were measured in all groups before diabetes induction and at the end of week 3. Oxidative stress was evaluated in the liver by measurement of malondialdehyde levels and total thiol concentration at the end of the experiment.Results: A significant increase in serum glucose and triglyceride levels was observed in diabetic rats, which was accompanied by increased malondialdehyde levels and decreased total thiol concentration in the liver after 3 weeks. Treatment of diabetic rats with R. turkestanicum rhizome extract at the doses of 200, 400 and 600 mg/kg over a 3-week period did not change serum glucose, hepatic malondialdehyde and total thiol levels in diabetic rats. However, treatment with R. turkestanicum extract significantly decreased serum triglyceride levels in a dose-dependent manner at the end of the experiment.Conclusion: R. turkestanicum rhizome extract possess anti-hypertriglyceridemic, but not hypoglycemic or hepatoprotective effect in diabetic rats. Therefore, R. turkestanicum rhizome should be consumed with more caution by diabetic patients.